Evaluation of Improved Hermaphrodite Papaya (Carica papaya L.) Varieties for Growth, Yield and Quality at Teppi, Southwestern Ethiopia - Sora, Shamil Alo; Guji, Merga Jibat (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The fruit with the most commercial significance in the Caricaceae family is the papaya (Carica papaya L.). The fruits are very valuable in terms of nutrition, economy, and medicine. One of the things restricting its production and productivity in Ethiopia is the lack of improved cultivars. In order to determine the optimum high yielding, pest and disease tolerant, variety/ies for the target area, this study was carried out to evaluate the performance of improved papaya varieties. Three newly released papaya varieties were brought to Teppi agricultural research center from Melkassa agricultural research center for evaluation over the cropping seasons of 2019/20 to 2020/21. The experiment was laid out in randomized complete block design and replicated three times. The mean yield was ranged from 34.24 to 90.08 t/ha for Braz-HS1 and Meki-HL1 varieties respectively. The findings of the study revealed that, based on the recorded parameters Meki-HL1 variety performed better followed by Koka-HM1 variety and these two varieties will be recommended for the surrounding farmers for wider production. Further study should be carried out with improved varieties to improve papaya production and nutritional security as well, especially in southwestern Ethiopia.